Prediction of patient outcomes through social determinants of health: The Pulmonary Hypertension Association Registry (PHAR) evaluation. (28th July 2022) - Grinnan, Dan; Kang, Le; DeWilde, Christine; Badesch, David; Benza, Raymond; Bull, Todd; Chakinala, Murali; DeMarco, Teresa; Feldman, Jeremy; Ford, Hubert J.; Klinger, James; McConnell, John; et al.
Abstract: Outcomes of patients with pulmonary arterial hypertension (PAH) may be associated with social determinants of health (SDOH) and other baseline patient characteristics. At present, there is no prognostic model to predict important patient outcomes in PAH based on SDOH. Utilizing information from the Pulmonary Hypertension Association Registry (PHAR), we derive a model (PHAR Evaluation or PHARE) to predict an important composite patient outcomes based on SDOH and other patient characteristics. Baseline data regarding SDOH from adult patients with PAH enrolled in the PHAR between 2015 and March 23, 2020, were included for analysis. We performed repeated measures logistic regression modeling with dichotomous outcome data (0 for no events, 1 for one or more events) to derive the PHARE. Here, 1275 consecutive adult patients enrolled in the PHAR from 47 participating centers were included. Variables included in our model are race, gender, ethnicity, household income, level of education, age, body mass index, drug use, alcohol use, marital status, and type of health insurance. Interaction effect between variables was analyzed and several interactions were also included in the PHARE. The PHARE shows a c ‐statistic of 0.608 ( p < 0.0001) with 95% confidence intervals (0.583, 0.632). Using SDOH and baseline characteristics from the PHAR, the PHARE correlates with our composite patient outcome. Further work evaluating the role of SDOH in prognostic modeling of PAH is indicated.